A rapid method for peR amplification of specific genes of Mycobacterium avium sub sp. paratuberculosis - VIJAYARANI, K; KUMAMAN, K (The Indian Journal of Animal Sciences, 2011)
The present study describes a simple and rapid method for amplifying various genes of Mycobacterium aviLl1n subsp. paratuberculosis (MAP) by polymerase chain reaction. Culture supernatants of MAP, when used as template resulted in the amplification of IS 900, ISMav2, ISMap02, and superoxide dismutase genes of MAP. This Inethod circumvents the specific isolation of genomic DNA frOln concentrated MAP organisms for ainplifying MAP genes and saves valuable reagents and time. Â